Analisis Proksimat, Serat Pangan, dan Uji Organoleptik Beras Analog Umbi Yakon (Smallanthus sonchifolius) Substitusi Isolat Kedelai - Cut Ajma Fitria Hafifah; Dhafina Avriani; Kamilia Ramanda; Hikma Syafa Fuadah; Dalva Sania Azzahra; Lulu’ Luthfiya; Qothrunnadaa Fajr Rooiqoh (Universitas Airlangga, 2026)
Background: Yacon tubers are one of the tubers not widely cultivated in Indonesia, and have a low-calorie fructooligosaccharide content that has the potential to support obesity prevention. Soy protein isolate is also known to contain isoflavones that can help lower cholesterol levels. The potential of these two ingredients encourages the development of functional food-based analogue rice. Objective: To examine the effect of different treatments of several yacon tuber-based analogue rice formulas with soy isolate substitution on their nutritional content and hedonic characteristics. Methods: The experimental study used a Completely Randomized Design (CRD) with four soybean isolate substitution formulations and two replications. The variables measured included proximate variables (water, ash, protein, fat, carbohydrate), total dietary fiber, and organoleptic tests (color, aroma, and texture) using a hedonic test by 28 semi-trained panelists. Proximate data were analyzed using One-Way ANOVA and Duncan’s test, while hedonic data were analyzed using the Kruskal-Wallis and Mann-Whitney tests. Results: There were significant differences in nutritional content and hedonic assessment between formulations. Formulation F2 received the highest preference for colour and texture, while F3 received the highest preference for aroma. Nutritionally, formulation F4 showed the most superior composition, especially in terms of total dietary fibre content, which was higher than that of commercial rice. Conclusions: Formula F2 was the best in terms of acceptability to panelists, while formula F4 was the best in terms of nutrition, particularly its fibre content.